Coriandrum sativum and Aloysia triphylla can Protect the Development of Cancer: An in Vivo Study using Mouse Painting Assay - Khabour, Omar F.; Abuhammad, Sawsan; Alzoubi, Karem H.; Alkofahi, Ahmad S. (Current Cancer Drug Targets, 2024)
Aim: The aim of this study is to examine the protective properties of Coriandrum sativum and Aloysia triphylla against the development of skin cancer. Methods: The skin cancer balb/c mouse model was utilized in the study. Plant extracts were administered to animals using oral gavage. In addition, skin cancer was induced using 7,12-dimethylbenz( a) anthracene (DMBA). Results: The study found that A. triphylla extract reduced both tumor incidence (P<0.01) and papilloma frequency (P<0.001) and delayed the onset of tumor development (P<0.001). The A. triphylla extract did not affect tumor size in animals. C. sativum leaf extract reduced the number of tumors per animal, the incidence of tumors, and the frequency of papilloma (P<0.05). In addition, it delayed (P<0.01) the onset of tumors. Treatment of animals with C. sativum seed extract reduced the frequency of papilloma (P<0.05) and delayed the onset of tumors (P<0.05). However, the examined plant extracts did not impact the size of tumors induced by DMBA (P>0.05). Conclusion: The findings of this study revealed that C. sativum and A. triphylla could protect against cancer development as indicated using the animal model of skin painting assay.
Keywords: skin painting assay